Football Fandom and Migration : An Ethnography of Transnational Practices and Narratives in Vienna and Istanbul - Szogs, Nina (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book studies how transnationalisation, Europeanisation and migration processes intersect with football fandom, through an analysis of the transnational narratives and practices of Fenerbahçe and Galatasaray football fans in Vienna, Austria. Based on ethnographic fieldwork in Austria, Turkey and Germany, the author analyses the ways in which narratives about football fandom are often linked to migrant experiences, including practices of (self-)culturalization in the diasporic context in Austria. The book shows how constructed ethnicities and also masculinities and femininities meet in football fan performances and in the construction of what makes a "proper" football fan. Turkish football fandom is a field where powerful prejudices and stereotypes amalgamate and interact. This study enables the reader to look into migration processes and discussions about related topics from a different angle: the love of a football club. Football Fandom and Migration <will be="" of="" interest="" to="" students="" and="" scholars="" across="" a="" range="" disciplines,="" including="" anthropology,="" sociology,="" european="" studies,="" political="" sciences,="" gender="" leisure="" sport="" sociology="" history. .
Keywords: Social sciences.; Ethnology.; Sports -- Sociological aspects.; Emigration and immigration.; elektronické knihy; electronic books